KEBIJAKAN PROGRAM 100 PASANGAN NIKAH GRATIS PEMERINTAH KOTA PEKANBARU DI KUA KECAMATAN TAMPAN DALAM MENDUKUNG PENGUATAN KETAHANAN KELUARGA BERBASIS NILAI RELIGIUS - Afrinaldy Rustam (Hawa : Jurnal Pemberdayaan Dan Pengabdian Masyarakat, 2026)
The 100 Free Marriage Program organized by the Pekanbaru City Government is one of the strategic policies aimed at strengthening family resilience based on religious values. This program seeks to expand public access to marriage services that are legally recognized both religiously and by the state, particularly for economically disadvantaged communities. This study aims to analyze the implementation of the free marriage policy program at the Office of Religious Affairs (KUA) of Tampan District and its contribution to optimizing family resilience.The research employed a qualitative method with a descriptive-analytical approach through document studies and literature reviews. The findings indicate that the free marriage program not only alleviates the economic burden on the community but also strengthens the role of the KUA in premarital guidance and the internalization of Islamic values. Furthermore, the program contributes positively to preventing unregistered marriages and improving couples’ readiness to build a sakinah, mawaddah, and rahmah family.